Consumer behavior in Latin America : income and spending of families in ten Andean cities - Musgrove, Philip (Washington : Brookings Institution, 1978)
the book presents a comparative analysis of household income and spending based on new and relatively uniform survey data, for ten cities in five South American countries.
"An ECIEL study."
Includes bibliographical references and index.
asm 24/01/2019
Loans
Keywords: Income; Consumption (Economics); Consumer behavior; Cost and standard of living